1986
DOI: 10.1093/ajcn/44.3.362
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutritional status associated with obstructive jaundice and biliary drainage in rats

Abstract: Effect of bile duct ligation (BDL) and internal biliary drainage on food intake and nutritional status was studied in rats and compared with sham and pair-fed animals. During week 1, food intake of BDL animals was reduced (p less than 0.05), resulting in weight loss (p less than 0.05). In weeks 2 and 3, food intake, nitrogen balance, and weight gain were similar in all groups. Internal biliary drainage or sham operation after 3 wk produced transient changes in food intake and N2 balance. Serum albumin fell in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 26 publications
3
33
0
3
Order By: Relevance
“…However, for a number of reasons this possibility seems unlikely. First, previous studies have shown that rats with BDL do not suffer from any negative nitrogen balance during the first 2-3 wk after ligation, when biliary obstruction-associated endotoxemia and/or sepsis usually occur (7,20,45). In contrast, 5 wk after BDL, when biliary cirrhosis has fully developed, muscle proteolysis is increased, as found in this study.…”
Section: Discussionsupporting
confidence: 77%
“…However, for a number of reasons this possibility seems unlikely. First, previous studies have shown that rats with BDL do not suffer from any negative nitrogen balance during the first 2-3 wk after ligation, when biliary obstruction-associated endotoxemia and/or sepsis usually occur (7,20,45). In contrast, 5 wk after BDL, when biliary cirrhosis has fully developed, muscle proteolysis is increased, as found in this study.…”
Section: Discussionsupporting
confidence: 77%
“…20,26,[34][35][36][37][38] Mortality was significantly reduced in these animal models. With respect to the preferred route of drainage, internal PBD was found to be superior to external PBD in terms of reduction in endotoxemia and mortality by some, whereas others demonstrated external drainage, although in the shortterm, to lead to a better recovery of cellular immunity than internal drainage.…”
Section: Biliary Drainagementioning
confidence: 85%
“…Weight gain and ingested feed have been frequently used in the evaluation of the nutritional state of animals submitted to ligature of the common bile duct 24,25 . However, we found no references in the literature on the feed energy utilization of this model.…”
Section: Weight Gain Total Quantity Of Ingested Feed and Feed Energymentioning
confidence: 99%
“…Sokal et al 25 , studied rats with obstructive cholestasis induced by ligature and common bile duct resection, and observed that from P30 to P62 a significant reduction in body weight and feed ingestion occurred, when compared to the control group with sham operation. In another study, Gouma et al 24 evaluated adult rats weighing 285 to 320g submitted to double ligature of the common bile duct, and concluded that they presented a reduction in feed ingestion.…”
Section: Weight Gain Total Quantity Of Ingested Feed and Feed Energymentioning
confidence: 99%